Bulk Defects Passivation of Tin Halide Perovskite by Tin Thiocyanate - Matteo Pitaro; Lorenzo Di Mario; Jacopo Pinna; Diego A. Acevedo‐Guzmán; Marios Neophytou; Mindaugas Kirkus; Thomas D. Anthopoulos; Giuseppe Portale; Petra Rudolf; Maria Antonietta Loi (Carbon Energy, 2025)
ABSTRACT Despite the rapid efficiency increase, tin halide perovskite solar cells are significantly behind their lead‐based counterpart, with the highest reported efficiency of 15.38%. The main reason for this large difference is attributed to the instability of Sn2+, which easily oxidizes to Sn4+, creating Sn vacancies and increasing the open‐circuit voltage loss. In this work, we implemented tin thiocyanate (Sn(SCN)2) as an additive for passivating the bulk defects of a germanium‐doped tin halide perovskite film. Adding Sn2+ and SCN− ions reduces the Sn and iodine vacancies, limiting non‐radiative recombination and favoring longer charge‐carrier dynamics. Moreover, the addition of Sn(SCN)2 induces a higher film crystallinity and preferential orientation of the (l00) planes parallel to the substrate. The passivated devices showed improved photovoltaic parameters with the best open‐circuit voltage of 0.716 V and the best efficiency of 12.22%, compared to 0.647 V and 10.2% for the reference device. In addition, the passivated solar cell retains 88.7% of its initial efficiency after 80 min of illumination under 100 mW cm‐2 and is substantially better than the control device, which reaches 82.6% of its initial power conversion efficiency only after 30 min. This work demonstrates the passivation potential of tin‐based additives, which combined with different counterions give a relatively large space of choices for passivation of Sn‐based perovskites.